Simple model and integral method for simulating the growth of the borided layer FeB/Fe2B on the AISI H13 steel - Youcef Djafri; Bendaoud Mebarek; Guerri Yassine El; Mourad Keddam; Naima Hadjadj (Zaštita Materijala)
The prediction of boride layer growth kinetics requires the development of a mathematical model. In the present study, two diffusion models (a simple model and an integral method-based model) were proposed to investigate the boriding kinetics of pack-borided AISI H13 steel. These two diffusion models did not consider the effect of boride incubation times of the total boride layer (FeB + Fe2B). The diffusion coefficients of boron in the FeB and Fe2B layers were estimated using the proposed integral method-based model. Additionally, the growth rate constants were determined and the layer thickness was calculated after finding the needed parameters. The results obtained were compared to the experimental ones taken from the work of Nait Abdellah et al.[4] and a good agreement has been noticed. Finally, the mass gain has been calculated for both phases, showing that of FeB increased more compared to that of Fe2B over time.